2003
DOI: 10.3141/1857-04
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Integrated Lane-Changing Behavior

Abstract: The lane-changing model is an important component within microscopic traffic simulation tools. Following the emergence of these tools in recent years, interest in the development of more reliable lane-changing models has increased. Lane-changing behavior is also important in several other applications such as capacity analysis and safety studies. Lane-changing behavior is usually modeled in two steps: (a) the decision to consider a lane change, and (b) the decision to execute the lane change. In most models, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
140
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(144 citation statements)
references
References 4 publications
2
140
0
2
Order By: Relevance
“…The stateof-the-art in lane-changing models includes Gipps (1986), Hidas (2002Hidas ( , 2005 and Toledo et al (2005Toledo et al ( , 2003. For an overview of lane changing models see Toledo (2007) or Janson Olstam (2005).…”
Section: Lane-changingmentioning
confidence: 99%
“…The stateof-the-art in lane-changing models includes Gipps (1986), Hidas (2002Hidas ( , 2005 and Toledo et al (2005Toledo et al ( , 2003. For an overview of lane changing models see Toledo (2007) or Janson Olstam (2005).…”
Section: Lane-changingmentioning
confidence: 99%
“…From Figure 9, we can see that the Weibull distribution well fits the merging probability distribution of the critical gap in both LA and SH. This result can be applied to microscopic traffic simulation, where the Weibull distribution could be more appropriate than the lognormal distribution [17]. Furthermore, the critical gap which is stochastic can help to explain free, forced, and cooperative lane changing [22,23].…”
Section: Merging Probability Function With Respect To Critical Gap Letmentioning
confidence: 99%
“…Current simulation models, such as MITSIM [17], CORSIM [18], VISSIM [19], and TransModeler [20], use critical gaps in different ways. For example, risk factors are used to define the critical gaps in CORSIM; and a psychophysical model is used in VISSIM to obtain a critical gap.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The critical gap was generally defined as the minimum value of the accepted gap. Furthermore, past research (Ahmed et al, 1996;Toledo et al, 2003) indicated that the size of the accepted gap could vary with the speed of the subject vehicle, its lead and lag vehicle, the longitudinal inter-vehicle' spacing, traffic conditions, and driver characteristics, etc. Therefore, the concept of accepted gap and critical gap were adopted in this study to develop a safety gap prediction model for potential application in the development of lane-change support systems.…”
Section: Introductionmentioning
confidence: 99%
“…Many traffic-flow simulation models applied Gipps' lane-change decision model to simulate vehicle lane-change maneuvers. In CORSIM (FHWA, 1998) and some major research (Ahmed, Ben-Akiva, Koutsopoulos, & Mishalani, 1996;Toledo, Koutsopoulos, & Ben-Akiva, 2003) the types of lane change were classified as either mandatory or discretionary. Mandatory lane change logic was applied to a driver when the driver was required to leave the current lane; discretionary lane change logic was used when the driver perceived the driving conditions in the target lane to be better, although a lane change was not required.…”
Section: Introductionmentioning
confidence: 99%